Multiple Myeloma and Other Plasma Cell Neoplasms (Hematologic Malignancies,, 2018)
This book is a comprehensive source of up-to-date information on plasma cell neoplasms. Key features include the provision of new criteria for the diagnosis of symptomatic multiple myeloma requiring treatment and the description of novel therapies for myeloma and other plasma cell neoplasms that have only very recently been licensed by the U.S. Food and Drug Administration. Examples include lenalidomide as first-line therapy, panobinostat in combination with bortezomib plus dexamethasone for relapsed/refractory myeloma, ibrutinib for Waldenström's macroglobulinemia, and new therapeutic regimens for systemic amyloidosis and POEMS syndrome. Information is also provided on drug combinations that have shown encouraging results and are very near to approval. Other important aspects covered in the book are the role of different imaging modalities in workup and the significance of newly acquired data relating to prognosis and minimal residual disease. Readers will find Multiple Myeloma and Other Plasma Cell Neoplasms to be a rich source of knowledge that will be invaluable in improving patient management. .